KEBERGANTUNGAN TEMPERATUR PLASMA HIDROGEN DALAM TEKANAN RENDAH - Siti Nurul Alifah; Saktioto Saktioto (Komunikasi Fisika Indonesia, 2019)
The density and reaction rate values of plasma are physical quantities needed to produce plasma hydrogen. Both are needed to estimate the heat and the operating time of plasma generator. Density and reaction rate of plasma values are obtained by computational modeling using the continuity and Arrhenius equation. Five spesies of hydrogen are used in this research i.e electron, H2, H2+, H and H+. The pressure used was 9.7 mTorr and the temperature of electron used is higher than the temperatures of the hydrogen species. The temperatures scale used in high at 34812 Kelvin for electron and 9283.2 for other species. The study resulted that hydrogen gas can be plasma when it reaches the time span 3.8x10-7second. The equilibrium conditions last for 10-3 second after the time limit be returned as plasma gas. The result of density for each species at range 1016 until 1018 m-3. The value of the fastest reaction rate equal to 7,3 x 1053 m-3 s-1.